Broad-spectrum ubiquitin-specific protease inhibition as a mechanism for the cytotoxicity of YM155 in cancers - Xiang Li; Na He; Yan Lv; Haiyue Wang; Ming Zhang; Heiyan Zhai; Zhen Yang; Yi Yang; Dagang Guo; Zhixiang Cao; Yiyou Chen (Scientific Reports)
Abstract Protein ubiquitination is a dynamic and reversible process involved in gene transcription, protein metabolism, and cellular apoptosis. Ubiquitin specific proteases (USPs), as the largest family of deubiquitinating enzymes, are able to remove the ubiquitin from target proteins, rescuing them from degradation. Here, we characterized the small molecule antitumor agent YM155 as a broad-spectrum USP inhibitor. By inhibiting the deubiquitinase activity of multiple USPs, YM155 causes the degradation of oncogenic substrate proteins, such as c-Myc and intracellular domain of Notch1. In cancers driven by these proteins, YM155 induces profound cell apoptosis and markedly inhibits tumor growth in xenograft models. Together, these findings demonstrate that YM155 is a broad-spectrum USP inhibitor, and a potential drug candidate for cancers which depend on hyper-active oncogenic proteins that are regulated by the ubiquitin-proteasome pathway.